Extraosseous Calcification of the Esophagus: Clinicopathologic Correlates of Esophageal Mucosal Calcinosis. Issue 1 (2017) - Garber, Ari; Arora, Zubin; Welch, Nicole; Lapinski, James; Burke, Carol A.
ABSTRACT : N/A: Esophageal mucosal calcinosis (EMC) is a rare cause of dysphagia with high morbidity. We present a patient who experienced melena and 3 months of solid and liquid dysphagia along with bilateral lower extremity pain, erythema, and edema later determined to be calcific uremic arteriolopathy (CUA), or calciphylaxis. An esophagogastroduodenoscopy revealed nodularity and linear ulcerations in the upper third of the esophagus. Histology showed active inflammation and ulceration with small foci of subepithelial and intraepithelial calcification consistent with EMC. There is no known treatment for this disorder. Sodium thiosulfate, typically used to treat CUA, did not improve her dysphagia.